PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS DIGITAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V SDN 2 LAMCOT - Darrosa, Fitria; Yusuf, Nidar; Ibrahimi, Raziska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The mathematical ability of elementary school students in Indonesia remains low, with Indonesia ranking 70th out of 81 countries in PISA 2022. One of the problems faced is that fifth grade students experience difficulties in understanding fraction material, which is caused by the limited use of technology-based interactive learning media. This research aims to determine the development process and effectiveness of digital-based flashcard learning media in improving the mathematical concept understanding of fifth grade students at SDN 2 Lamcot on fraction material. This research uses the Research and Development method with the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 23 fifth grade students at SDN 2 Lamcot. Data collection techniques used interviews, expert validation questionnaires, student response questionnaires, and tests. The research results show that the media development process was carried out systematically through the five ADDIE stages and produced a highly feasible product based on a combined validation of 96.43%. Digital-based flashcard media proved to be highly effective in improving students' mathematical concept understanding, evidenced by a practicality test of 88.04% (very practical) and a significant improvement in learning outcomes from a pretest average of 46.09 to a posttest of 86,95, with the completion percentage increasing from 8.7% to 100%. This media is able to create engaging, interactive, and meaningful learning for students.